FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PHBS PADA MAHASISWA FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS AHMAD DAHLAN - Nisa Alya Fadhila; Ahmad Faizal Rangkuti (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2021)
Health is a right for every human being. Maintaining, maintaining and improving is a way that health can benefit oneself, family and society. Health behavior can be achieved through awareness as in the application of clean and healthy living behavior (PHBS) where the principle of implementation is prevention is better than cure. The purpose of the study was to determine the factors associated with clean and healthy living behavior in FKM UAD students. This type of research uses quantitative research with analytical methods and cross sectional research design. The sample of this study was FKM UAD students with a total of 158 students who were carried out using a total sampling technique. The research instrument used was an online questionnaire which was distributed via google form. The data analysis used was univariate analysis and bivariate analysis with Chi Square statistical test. The results of the univariate analysis showed that as many as 127 (80.45%) students, the majority were female, 80 (50.6%) students had pocket money <Rp.1.360.000, as many as 155 (98.1%) students the majority have a positive attitude, and as many as 143 (90.5%) students behave well. While the results of the bivariate analysis obtained sex with clean and healthy living behavior p value = 0.176, pocket money with clean and healthy living behavior p value = 0.582, and attitudes with clean and healthy living behavior healthy p value = 0.260. There is no relationship between gender and clean and healthy living behavior, there is no relationship between pocket money and clean and healthy living behavior and clean and healthy living behavior, no there is a relationship between attitude and clean and healthy living behavior.